(untitled) (Journal of Asian Development Studies, 2024)
Enhancing employee performance involves setting clear expectations and providing continuous feedback. It is essential to create a positive workplace. This study creates the necessity of performance appraisal activities to improve employee performance and achieve organizational goals. It investigates the impact of performance appraisal on employee performance in Higher Education Institutions (HEIs) in Sindh, Pakistan. Structural Equation Modeling (SEM) was employed using SmartPLS to analyze the relationships between variables. It includes Performance Appraisal, Organizational Commitment, Job Involvement, and Employee Performance. A sample of 127 participants was selected from various HEIs in Sindh, Pakistan. The findings reveal a significant mediating effect of organizational commitment and job involvement on the relationship between performance appraisal and employee performance. On the other hand, effective performance appraisals enhance employee performance when supported by strong organizational commitment and job involvement. It includes recommendations that hold valuable knowledge and implications for executive bodies and policymakers of HEIs.